T Cell Polarization toward TH2/TFH2 and TH17/TFH17 in Patients with IgG4-Related Disease - Grados, Aurélie; Ebbo, Mikael; Piperoglou, Christelle; Groh, Matthieu; Regent, Alexis; Samson, Maxime; Terrier, Benjamin; Loundou, Anderson; Morel, Nathalie; Audia, Sylvain; Maurier, François; Graveleau, Julie; et al. (Frontiers in Immunology, 2017)
We examine and characterize subsets of circulating lymphocytes in untreated patients with active IgG4-related disease (IgG4-RD). Twenty eight consecutive patients with proven IgG4-RD were included in a prospective, multicentric study. Lymphocytes subsets were analyzed by flow cytometry, with analysis of TH1/TH2/TH17, TFH cells and cytokine release by peripheral blood mononuclear cells. Results were compared with healthy controls and with patients with primary Sjogren syndrome. Patients with IgG4-RD were characterized by an increase in circulating T regulatory cells, TH2, TH17 and the CD4+CXCR5+PD1+ TFH subset. Accordingly, cytokine release was associated with increased levels of IL-10 and IL-4. TFH increase was characterized by specific expansion of TFH2 (CCR6- CXCR3-), and to a lesser extend TFH17 (CCR6+CXCR3-) cells. The CD4+CXCR5+PD1+ TFH cells normalized under treatment. We conclude that the functional orientation of circulating T cells towards a TH2/TFH2 and TH17/TFH17 profile is implicated in the pathophysiology of IgG4-RD. New treatment approaches should focus on targeting specific T cell changes in patients with IgG4-RD.□